Evaluation of the health promotion effect of hepatitis B prevention and treatment in the Zhejiang demonstration area, China - Hongli Qin; Yan Qiu; Meike Ying; Jingjing Ren (BMC, 2022)
Abstract Background To investigate the health literacy level and health promotion effect of hepatitis B prevention and treatment in the demonstration area of Zhejiang Province. Methods The National Science and Technology Major Health Education Group took 6 demonstration areas in Zhejiang Province as the whole research site. After the sample size (N=2160 people) was determined, a multistage stratified cluster sampling method was used to conduct a questionnaire survey in 2018 (before health education) and 2019 (after health education). Stata 12 statistical software was used to analyse the status and improvement rate of hepatitis B health literacy of residents in the demonstration area before and after health education and compare the health promotion effects of different health intervention methods. Results Before and after health education, there was no significant difference in the basic information of the subjects (P>0.05). After the health education intervention, the level of hepatitis B health literacy of residents in the demonstration area increased by 11.8%, and the difference was statistically significant (P < 0.001). The awareness rate of hepatitis B transmission was low before health education but increased after health education. The form of "Internet +" health education may better improve the residents' health literacy level about hepatitis B prevention and treatment. Conclusion After health education, the level of health literacy of residents in the Zhejiang demonstration area about hepatitis B prevention and control significantly improved, but there is room for further improvement. In the future, targeted health education intervention should be carried out, and the health education mode of "Internet +" can achieve better results to effectively prevent and control hepatitis B.